Special Features of Consumption of Water and Drinks by Kazakhstan Athletes - Yeldana Yerzhanova; Zhanna Sabyrbek; Zhanna Kalmatayeva; Kazys Milasius (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
In Kazakhstan, the regime and habits of consuming liquids by athletes in various sports have not been suffi ciently explored yet. The purpose of the study is to determine the amount, schedule and characteristics of consumption of drinks by sportsmen after the example of diff erent sports. In 2017 15 volleyball players of the Burevestnik team in Almaty, 15 judo wrestlers of the national team of Kazakhstan, 15 wrestlers of the club team and 15 triathletes of the national team of Kazakhstan took part in the estimation of the regime of water and other liquids consumption. A valid questionnaire was used to study the data on the volume and water consumption schedule and other liquids. The amount of water and other drinks consumed was studied by reproducing drinking during 24 hours. The questionnaire put questions about the amount of water and beverages consumed prior to training, during and after it, and furthermore certain types of beverages were determined. Our research showed that 63.34% of the Kazakhstan athletes under examination drink the recommended norm (2-3 liters per day), another 6.69% of the investigated consume from 3 to 6 liters of liquid. The researched athletes do not consume enough liquid 2 hours before training. Only 20% of volleyball players, judoists and triathletes of national teams consume the recommended norm of liquid (400-600 ml). Most of the investigated athletes consume necessary amount of water and other beverages during training. 70.0% of respondents drink water and juices during training, and only 16.7% of them drink sport drinks.